(untitled) - Cooper, William S. (Cambridge, UK, 2001)
In this book, William S. Cooper outlines a theory of rationality in which logical law emerges as an intrinsic aspect of evolutionary biology. He examines the connections between logic and evolutionary biology and illustrates how logical rules are derived directly from evolutionary principles, and therefore, have no independent status of their own. This biological perspective on logic, though at present unorthodox, could change traditional ideas about the reasoning process.
Keywords: Biology,Logic,Sinh học,Logic học; Philosophy,Triết lý